Germanium Junctionless MOSFET with Steep Subthreshold Swing. (27th March 2015) - Gupta, Manish; Kranti, Abhinav
Abstract : In this work, we analyze the occurrence of steep subthreshold swing ( S -swing) in Double Gate (DG) Germanium (Ge) Junctionless (JL) nMOS transistors. The performance of Ge JL transistor is compared with that of Si based JL MOSFETs. Our results show that it is possible to achieve steep S -swing < 1 mV/decade along with a steep current transition of nearly 3.5 orders at drain bias of 1.3 V in Ge JL MOSFETs. The work explores the feasibility of the occurrence of steep S -swing, and establishes an understanding of the advantages and challenges associated with Ge JL MOSFETs.